Perlindungan Hukum Bagi Para Pelaku Usaha Waralaba/Franchise Yang Mengalami Kerugian Akibat Wanprestasi - Patricius, Priscilla Trinita; Urbanisasi, Urbanisasi (Peneliti.net, 2023)
In a franchise business activity, it is necessary to have a binding agreement between the two parties, so that each party can determine the contents of the franchise business agreement itself, and also they can carry out the achievements in an agreement. parties who are reluctant to enter into an agreement are also bound by law because in carrying out an activity, one of which is a franchise activity which contains the second important matters that must be fulfilled in fulfilling a franchise business. If one of the parties does not make achievements in the franchise activity, it can be said to be an act of default. So that by saying a default, one of the parties can be sued or sued so that the party who suffers a loss can be asked for justice.